La Rit-macchina e la Piattaforma: Studio su Netflix - Ricciardi, Antonio (Mediascapes journal, 2024)
The birth of cybernetics, starting with the Macy Conferences and Wiener's early works, has provided a decisive contribution to the development of a concept of machine capable of overcoming the limits of pure and simple instrumentality. If the so-called first-order cybernetics, however, has thought the machine and its ontology within the narrow limits of a homeostatic, closed and self-sufficient system, second-order cybernetics has expanded this concept, extending the idea of ​​the machine to that of a system, inserting it in a regime of constant interaction and iteration: a real machine between machines. Nevertheless, it was not possible, in the classical cybernetic context, to think of the constitution of an authentic machinic proto-subjectivity. It will only be in the works of Felix Guattari (Guattari 2020 & 2022) that we will see the birth of ​​a machine (and of a real machinism) capable of assuming this theoretical consistency. In this context, the proto-subjectivity will be that of an abstract machine which, going beyond the material limits of the technical machine, transversely intersects all the elements of the concrete assemblage within which it operates. The abstract machine dynamizes all the components it articulates, dragging them into a real rhythmology, giving rise to what Kodwo Eshun (2019) defines as a rhythmachine. It is not simply a question of a new way of thinking the technical machine: rather, what is at stake here will be the idea of ​​a reality conceived sub specie machinae. On the basis of this Guattarian machinism we will try to build a general theory of the machine by examining a very specific case study: the Netflix platform. In this sense, first of all, we will see to what extent the Guattarian machine differs as much from that of Wiener and Ashby, as from that of Maturana and Varela. Once we have defined this scenario, we will move on to the analysis of the Netflix machine. Here, a detailed genealogy of the platform will be followed by an analysis of its rhyth-machinic nature. The final aim of the work will be to identify the fundamental traits that distinguish the rhythmachine from the machinic concepts elaborated within the first and second cybernetics.